2016
DOI: 10.1016/j.celrep.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Memory Formation by the Transcription Factor XBP1

Abstract: Contextual memory formation relies on the induction of new genes in the hippocampus. A polymorphism in the promoter of the transcription factor XBP1 was identified as a risk factor for Alzheimer's disease and bipolar disorders. XBP1 is a major regulator of the unfolded protein response (UPR), mediating adaptation to endoplasmic reticulum (ER) stress. Using a phenotypic screen, we uncovered an unexpected function of XBP1 in cognition and behavior. Mice lacking XBP1 in the nervous system showed specific impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 53 publications
3
122
1
2
Order By: Relevance
“…At least 5 TFBS sites were colocated with CpG46 in the human IDS promoter region which may contribute to the high expression of this gene in human nerve and brain tissues (Table 4). Of special interest among these transcription factor binding sites were the following: BACH1 and BACH2 have been recognized as members of the BTB-basic region leucine zipper transcription factor family which downregulate cell proliferation of neuroblastoma cells (Shim et al 2006); AP1 is constitutively upregulated in activated microglia and during the pathogenesis of Parkinson’s disease (Pal et al 2016); NFE2 has been shown to participate in the developmental regulation of the brain in zebrafish embryos (Williams et al 2013); and XBP1 has been identified as a risk factor for Alzheimer’s disease and bipolar disorders, contributing to impairment of contextual memory formation (Martinez et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…At least 5 TFBS sites were colocated with CpG46 in the human IDS promoter region which may contribute to the high expression of this gene in human nerve and brain tissues (Table 4). Of special interest among these transcription factor binding sites were the following: BACH1 and BACH2 have been recognized as members of the BTB-basic region leucine zipper transcription factor family which downregulate cell proliferation of neuroblastoma cells (Shim et al 2006); AP1 is constitutively upregulated in activated microglia and during the pathogenesis of Parkinson’s disease (Pal et al 2016); NFE2 has been shown to participate in the developmental regulation of the brain in zebrafish embryos (Williams et al 2013); and XBP1 has been identified as a risk factor for Alzheimer’s disease and bipolar disorders, contributing to impairment of contextual memory formation (Martinez et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Thus, previous studies showed that XBP-1s protected against Aβ-associated toxicity30 and could interfere with autophagy process67. More importantly and related to Alzheimer’s disease, XBP1 depletion revealed memory defects in wild-type mice29 and XBP-1s expression restored synaptic plasticity and memory control in several AD mice models62. Finally, XBP-1S transcriptionally up-regulates ADAM10, the α-secretase constitutive activity involved in the protective non amyloidogenic βAPP processing pathway60.…”
Section: Discussionmentioning
confidence: 96%
“…Besides its well established function in UPR signaling, XBP-1s transcription factor has been implicated in additional physiological functions including glucose and lipid metabolism control but could also be modulated in neurodegenerative diseases including AD2728. Interestingly, XBP-1s was recently shown to regulate memory formation29.…”
mentioning
confidence: 99%
“…The reduction of BACE1 level is mediated through the ubiquitin-ligase 3-hydroxy-3-methylglutaryl-coenzyme A reductase degradation 1 (HRD1) (47) which is also involved in APP degradation and the subsequent reduction in Aβ production (48). Moreover, sXBP1 enhances memory formation possibly by increasing the production of brainderived neurotrophic factor (BDNF) in the CNS (49). In addition to these mechanisms, sXBP1-induced BECN1 activation and subsequent activation of autophagy may be one of the mechanisms for ameliorating AD pathology (Fig.…”
Section: Xbp1 and Neurodegenerative Diseasesmentioning
confidence: 99%